Dispersion behavior and safety study of liquid hydrogen leakage under different application situations. (6th November 2020) - Tang, Xin; Pu, Liang; Shao, Xiangyu; Lei, Gang; Li, Yanzhong; Wang, Xinke
Abstract: The potential hazard of liquid hydrogen is still a problem for hydrogen-energy-driven automobile application. Based on the previous multicomponent-phase-change modeling of cryogenic and combustible liquids leakage. This paper has developed three different physical models to simulate the evaporation and dispersion processes of the liquid hydrogen (as vehicle fuel) that is leaking in open area, garage and tunnel scenarios. The leakage liquid hydrogen is 5.6 kg with a horizontal release direction on the ground. Cloud shape, duration time and hazard ranges are analyzed during the period of hydrogen cloud growing and shrinking in different environments. The results indicate that the case in open area displays the greatest flammable cloud volume among these three scenarios with 1133 m 3 in ignition hazard and 356 m 3 in detonation hazard, but the cloud mainly disperses above the height of 1.5 m, and it lasts for the shortest duration. Therefore, it would relatively safer than other two scenarios. The garage scenario has the longest dispersion duration time of 83.4 s for ignition and 30 s for detonation, and the widespread hazard ranges can put threat to all cars in the garage. The tunnel case shows the maximum downwind hazard distances below the height of 1.5 m. The corresponding ignition and detonation distances are 26.8 m and 24.4 m. Highlights: Physical models of open area, garage and tunnel scenarios are developed. Dispersion behaviors of hydrogen in different applied situations are investigated. Safety analysis of ignition/detonation clouds are compared. Safety suggestions for liquid hydrogen application in different situations are made.